Effect of Bolt Preload and Friction Coefficient on Slip Capacity and Yield in Steel Truss Bridge Connections - Tologana, Ricky Nofrianto; Triwiyono, Andreas; Sulistiyo, Djoko (Universitas Ibn Khaldun Bogor, 2025)
This study analyzes the effect of bolt preload and friction coefficient on slip capacity and yield in steel truss bridge connections using the finite element method (FEM) through Abaqus software. Preload variations ranging from 0.2 to 0.9 and friction coefficients between 0.3 and 0.5 were applied to find the relationship between these factors. The results indicate that increasing preload and friction coefficient enhances slip capacity. Specifically, at a preload of 0.2 and friction coefficient of 0.3, slip occurred at 1549.07 kN, whereas at a preload of 0.9 and friction coefficient of 0.5, the slip capacity reached 11354.1 kN. However, excessive preload (>0.7 ) can lead to local failure due to stress concentration around the bolt hole. Validation using the AISC analytical method showed an average difference of only 1.6% with a maximum error of 5.28%, indicating a high level of accuracy in the FEM model. These findings provide recommendations for optimal connection design, suggesting a preload of 0.7 and a friction coefficient of 0.5 to enhance connection capacity while mitigating the risk of premature failure